Criminalization and female incarceration as an expression of the social question in capitalist society - Roza Vieira, Greiceane (2023)
This article discusses the incarceration of women as a result of the capitalist society, considering for that matter the criminalization of the social issue. The critical literature that supports the investigated theme makes it possible to show that the criminalization of the social issue in Brazil has a deep connection with the historical construction of the notion of dangerous classes associated with a situation of poverty and social vulnerability. This was a quantitative cross-sectional study, of the analytical kind and with regional scope, with a descriptive statistical analysis, representing a topic investigated during an academic master's degree. The general objective was to understand how the capitalist mode of production and the reproduction of the social life originated by it affect the growing incarceration of women, using for that matter a previously collected database regarding women deprived of freedom in Rio Grande do Sul (RS). The results of the analysis showed the relevance of discussing the social issue, which expresses itself in the criminalization of poverty as a privileged focus of state agencies, exhibiting the material reality women in prison in RS have.